Transitioning a digital health innovation from research to routine practice: Two-way texting for male circumcision follow-up in Zimbabwe - Phiona Marongwe; Beatrice Wasunna; Jacqueline Gavera; Vernon Murenje; Farai Gwenzi; Joseph Hove; Christine Mauhy; Sinokuthemba Xaba; Raymond Mugwanya; Batsirai Makunike-Chikwinya; Tinashe Munyaradzi; Michael Korir; et al. (PLOS Digital Health, 2022)
Adult medical male circumcision (MC) is safe: global notifiable adverse event (AE) rates average below 2.0%. With Zimbabwe’s shortage of health care workers (HCWs) compounded by COVID-19 constraints, two-way text-based (2wT) MC follow-up may be advantageous over routinely scheduled in-person reviews. A 2019 randomized control trial (RCT) found 2wT to be safe and efficient for MC follow-up. As few digital health interventions successfully transition from RCT to scale, we detail the 2wT scale-up approach from RCT to routine MC practice comparing MC safety and efficiency outcomes. After the RCT, 2wT transitioned from a site-based (centralized) system to hub-and-spoke model for scale-up where one nurse triaged all 2wT patients, referring patients in need to their local clinic. No post-operative visits were required with 2wT. Routine patients were expected to attend at least one post-operative review. We compare 1) AEs and in-person visits between 2wT men from RCT and routine MC service delivery; and 2) 2wT-based and routine follow-up among adults during the 2wT scale-up period, January to October 2021. During scale-up period, 5084 of 17417 adult MC patients (29%) opted into 2wT. Of the 5084, 0.08% (95% CI: 0.03, 2.0) had an AE and 71.0% (95% CI: 69.7, 72.2) responded to ≥1 daily SMS, a significant decrease from the 1.9% AE rate (95% CI: 0.7, 3.6; p<0.001) and 92.5% response rate (95% CI: 89.0, 94.6; p<0.001) from 2wT RCT men. During scale-up, AE rates did not differ between routine (0.03%; 95% CI: 0.02, 0.08) and 2wT (p = 0.248) groups. Of 5084 2wT men, 630 (12.4%) received telehealth reassurance, wound care reminders, and hygiene advice via 2wT; 64 (19.7%) were referred for care of which 50% had visits. Similar to RCT outcomes, routine 2wT was safe and provided clear efficiency advantages over in-person follow-up. 2wT reduced unnecessary patient-provider contact for COVID-19 infection prevention. Rural network coverage, provider hesitancy, and the slow pace of MC guideline changes slowed 2wT expansion. However, immediate 2wT benefits for MC programs and potential benefits of 2wT-based telehealth for other health contexts outweigh limitations. Author summary Although digital health innovations hold promise to improve patient outcomes and reduce workload, there is very little evidence of success from routine settings in lower income countries. We successfully scaled a two-way texting (2wT) intervention from research to routine practice, providing men with SMS-based telehealth for male circumcision (MC) follow-up rather than requiring in-person reviews. 2wT operates without consistent connectivity, supports providers with decision-making tools, and requires patients to have only basic phones. Like in the research setting, 2wT reduced healthcare worker workload and maintained patient safety when implemented with routine MC teams. The COVID-19 pandemic led added urgency to 2wT expansion. We describe the successes and challenges of the 2wT scale-up, providing lessons learned that may enable others to adapt and adopt this open-source App in other health contexts that could benefit from a similar, low-cost, short-term, telehealth approach.